Nutritional status and common morbidities among school-going adolescents of rural areas of Vadodara, Gujarat: a cross sectional study - Modi, Prashant M.; Pathak, Sunil; Patel, Sagar; Srivastva, Ritika; Thomas, Reya; Khullar, Niharika (International Journal of Contemporary Pediatrics, 2019)
Background: Abnormal nutritional status i.e. underweight, overweight and obesity is increasing rapidly amongst adolescents irrespective of socioeconomic status and geography. This study was carried out to assess prevalence of abnormal nutritional status and common associated morbidities among school going adolescent of rural areas of Vadodara, Gujarat, India. Methods: A cross sectional observational study was done among school going adolescents of rural areas of Vadodara, Gujarat. A predesigned and pretested semi-structured proforma was used to get relevant clinical details of study participants. Total 474 students aged 12-17 years participated in our study. Results: Out of 474 enrolled adolescents, 16.67% were underweight, where as 3.8% and 2.95% were obese and overweight respectively. The prevalence of overweight and obesity were almost similar in both genders. Out of total 16.24% were stunted with predominance in boys compared to girls (p value: 0.039). Hypertension was found in 5.0% of participants with 3 times more prevalent in girls than boys (p value 0.011). Similarly, anemia was affecting both genders equally. Conclusions: Although underweight is a known nutritional problem of adolescents from rural areas, overweight and obesity are also rapidly growing health issues among them now a days. With keeping in mind this increasing burden of abnormal nutritional status and associated morbidities, regular health check-up, education of parents and adolescents on healthy lifestyle and inclusion of adolescents in existing government programmes are essential measures to reduce these problems.